2009
DOI: 10.1590/s1676-26492009000400004
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação transcultural para o português brasileiro do instrumento The Epilepsy Beliefs and Attitudes Scale (Ebas) - Adult Version

Abstract: INTRODUÇÃO: o desconhecimento acerca da epilepsia tem fomentado o interesse em desenvolver ferramentas voltadas para detecção das crenças e atitudes da comunidade em geral acerca da doença. OBJETIVO: apresentar o processo de adaptação transcultural do instrumento The Epilepsy Beliefs and Attitudes Scale (EBAS) - Adult Version e uma versão em português para uso no Brasil. MÉTODO: o processo de adaptação envolveu a equivalência conceitual, de itens, semântica e operacional. RESULTADOS: os conceitos apreendidos f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…After reading the story, participants were asked to select within a Likert scale of four points which of the following responses represent the intensity degree of belief for each item: (4) totally believe, (3) I strongly believe, (2) I believe a little (1) not at all [11]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading the story, participants were asked to select within a Likert scale of four points which of the following responses represent the intensity degree of belief for each item: (4) totally believe, (3) I strongly believe, (2) I believe a little (1) not at all [11]. …”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the concepts were considered relevant to Brazilian culture and the items were considered appropriate for the ability to represent these concepts in target population and showed good semantic equivalence comparing the final Portuguese version and the original [11]. …”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, participants were instructed to answer part II of the Brazilian version of The Epilepsy Beliefs and Attitudes Scale (EBAS) -Adult Version, in order to investigate their beliefs and attitudes towards childhood epilepsy [9].…”
Section: Methodsmentioning
confidence: 99%
“…The instrument is divided into: Part I with six questions addressing the participant's general knowledge and experience with epilepsy; Part II containing a story highlighting the symptoms and behaviors during and after an epileptic seizure in a child, followed by 46 beliefs and attitudes associated with childhood epilepsy [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation